Vaggione, R. P. (ed. y trad.): Eunomius. The extant works. XVII y 209 páginas. Oxford Early Christian Texts. Oxford, “at the Clarendon Press”, 1987. ISBN: 0-19-826814-9 - Fernández, Gonzalo (Gerión. Revista de Historia Antigua, 1988)
Sin resumen